EDGE EFFECT INFLUENCE TO REFLECTED IMPEDANCE OF EDDY-CURRENT PROBE - Закревський, О. (Proceedings of National Aviation University (archive), 2012)
This work is dedicated to solve analytically the edge effect Eddy-Current Probe (ECP) problem which helpto carry out mathematical research the edge effect influence to ECP precision and sensitivity ultrasonictransducer mechanical amplitude oscillation measurement mathematical research, pointed to cylindricalconductive objects radius control possibility with superimposed ECP.